Pengaruh pemberian air kotoran ikan dan biourin domba terhadap karakteristik fisiologi tanaman padi (Oryza sativa L.) Varietas inpari 32 - Winda Rianti; Bagus Dwi Herlianto; M.Ridwan; Rika Yayu Agustini (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
One of the factors that influences plants physiological processes is the absorption of nutrients obtained from both organic and inorganic fertilizers. Some organic fertilizers that can be given are fish waste water and sheep urine fertilizer. The aim of this research is to obtain information regarding the effect of fish waste water and sheep biourine on the physiological characteristics of rice plants (Oryza sativa L.) such as leaf chlorophyll content, Net Assimilation Rate (NAR) and Crop Growth Rate (CGR). This research was conducted on Agricultural Extension Field, Majalaya District, Karawang Regency, from January to April 2022. This experiment used an experimental method with a split plot design (Split Plot Design) with 10 treatment combinations which were repeated 3 times. The main plots are fish waste water (A): A1 (fish waste water), and A2 (ordinary irrigation water). As subplots for Sheep Biourine (P): P0 (Control), P1 (Factory Biourine 100 ml/l), P2 (Sheep Biourine 100 ml/l), P3 (Sheep Biourine 150 ml/l) and P4 (Sheep Biourine 200 ml /l). The research results showed that there was no interaction between biourine fertilizer treatment and fish waste water on the physiology characteristics of the rice plants (Oryza sativa L.).